Theoretical and experimental investigation of structural, spectroscopic, and thermal properties of Bismuth- and Gadolinium-doped hydroxyapatites - Ates, Tankut; Acar, Emine Nur; Barzinjy, Azeez A.; Koytepe, Suleyman; Keser, Serhat; Adam, Ibrahim Muhammad; Kaygili, Omer (Elsevier, 2026)
In this study, hydroxyapatite (HAp) materials doped with bismuth (Bi) and gadolinium (Gd) were synthesized using the wet chemical precipitation method and comprehensively characterized through both theoretical and experimental approaches. Density functional theory (DFT) calculations were employed to investigate the effects of co-doping with Bi and Gd on the electronic structure, lattice parameters, and unit cell volume. Results revealed a consistent reduction in bandgap energy with increasing dopant concentration, highlighting the tunability of HAp's electronic properties for advanced functional applications. Structural analyses revealed subtle reductions in lattice constants and unit cell volume, confirming the incorporation of dopants and lattice contraction. Experimental characterizations included X-ray diffraction (XRD), Fourier-transform infrared (FTIR) and Raman spectroscopy, thermal analyses (DTA/TGA), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). XRD confirmed phase purity with minor beta-TCP formation, while FTIR and Raman spectra validated the presence of phosphate and hydroxyl groups typical of HAp. Thermal analyses indicated excellent stability up to 900 degrees C with minimal mass loss, especially in doped samples. SEM images revealed nanostructured spherical morphologies with homogenous elemental distribution, while EDX confirmed the successful integration of Bi and Gd into the HAp lattice. Biocompatibility assays using l-929 fibroblast cells showed high cell viability (>80%) for all samples, indicating excellent biocompatibility with negligible cytotoxicity. Notably, Gd-doped and co-doped samples showed improved biological responses. These findings suggest that Bi/Gd co-doped HAp materials hold strong potential for biomedical applications such as bone implants and dental restorations, where enhanced electronic, thermal, and biocompatibility properties are crucial.
Keywords: Hydroxyapatite (HAp); Bismuth (Bi) doping; Gadolinium (Gd) doping; Thermal stability; Biocompatibility